Retraction: First viral replication of Covid-19 identified in the peritoneal dialysis fluid - Denis Fouque; Mathilde Nouvier (RDPLF, 2020)
Note editor : retraction of case report https://doi.org/10.25796/bdd.v3i1.54503 Dear Editor-in-chief, By this letter we would like to retract our case report entitled « First viral replication of Covid-19 identified in the peritoneal dialysis fluid of a symptomatic patient» that we submitted to your journal one week ago. We indeed wanted to inform the renal community of a potential presence of Covid-19 virus in the peritoneal dialysis fluid in patients undergoing peritoneal dialysis treatment. However, the patient general status impaired and he was transferred to an intensive care unit for acute myocardial insufficiency. During this stay, he was re-checked for a number of other organs alterations. A total of 7 RT-PCR SARS-Cov2 tests , validated by the National Reference Center, were done : 2 by nasopharyngeal swabs, 1 in bronchoalveolar lavage, 3 peritoneal dialysate and one in stool. A serological test was also performed. All tests were found negative. The CT scan was analyzed again by a specialized radiologist and although a COVID-19 pulmonary disease was likely, it was not possible to rule out a pulmonary edema secondary to an acute myocarditis of different origin. Therefore, based on these later information, and after careful discussion with the virologists, we think that the first positive PCR result was erroneous, without clear explanation for this. Until new cases appear, the fact that two subsequent peritoneal dialysate carefully processed were negative indicates that we cannot reliably prove a peritoneal dialysate contamination by COVID-19 virus in our patient. We deeply apologize for this premature publication. M.Nouvier and D.Fouque for the authors